The Behavioral Intentions of Muslim and Non-Muslim Customers Toward Bank Syariah Indonesia Products Post-Merger - Nizam, Ahmad; Saputra, Al Mahfud (Jurnal Economia, 2025)
AbstractThis study aims to evaluate the impact of the conversion and merger of Bank Syariah Indonesia (BSI) after the implementation of the Qanun that requires all financial institutions in Aceh to switch to sharia. The sample consisted of 300 Muslim and non-Muslim customers. Using the Theory of Reasoned Action (TRA) and Theory of Planned Behavior (TPB), the study analyzed changes in customer behavior in response to the regulation. The findings show that the conversion initially decreased customers' attitudes and subjective norms towards using BSI products, but increased post-merger. There is a difference between Muslim and non-Muslim customers' attitudes; non-Muslim customers support BSI products despite unfavorable subjective norms, while Muslim customers only show subjective norms without significant attitudes towards usage intention. These findings provide insights for IB service providers to design innovative services that accommodate different consumer attitudes and ensure comprehensive application of Islamic principles.